PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PELAKSANAAN FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI RIAU 2014-2019 - Fauzi Fauzi; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by failure of Regional houseRepresentatives (DPRD) of Riau Province to carried out function of establi shing regional regulations, budgetary functions and supervisory func tions. This was indicated by existence of regional regulations that make it diffic ult for c ommunity, waste of budg et by regional government and DPRD. In addition, the f ollow up of cases pl ant waste was not responsive and other case s have caused reactions from community, especiall ystudents. In the student raises a reaction in the form of discussion, audience, carrying out demonstrations that indicate that there were injustice s and irregular ities felt by community. Therefore, the researcher raised the research entitled